2014
DOI: 10.3892/mmr.2014.2528
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of respiratory impedance in patients with chronic obstructive pulmonary disease by an impulse oscillation system

Abstract: An impulse oscillometry system (IOS) assesses pulmonary resistance and reactance. The present study investigated which IOS measurement is correlated with airflow obstruction, airway conductance and lung volume in chronic obstructive pulmonary disease (COPD). A total of 180 patients with COPD were selected and 95 agreed to follow‑up 1 year after the initial tests. IOS measurements [R5, R20, X5 and resonant frequency (Fres)], body plethysmography [forced end‑expiratory flow (FEF)75, total lung capacity, residual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The compliance of COPD patients decreased overall, and a previous study has reported results consistent with ours 17. Furthermore, Gong et al20 demonstrated that X5, R5, and Fres are the IOS measurements most closely associated with more traditional measurements of pulmonary function in COPD patients. The associations between FEV 1 and the IOS measurements were as follows: X5 ( r =0.635), Fres ( r =−0.721), and R5 ( r =−0.496); these results were consistent with our results.…”
Section: Discussionsupporting
confidence: 85%
“…The compliance of COPD patients decreased overall, and a previous study has reported results consistent with ours 17. Furthermore, Gong et al20 demonstrated that X5, R5, and Fres are the IOS measurements most closely associated with more traditional measurements of pulmonary function in COPD patients. The associations between FEV 1 and the IOS measurements were as follows: X5 ( r =0.635), Fres ( r =−0.721), and R5 ( r =−0.496); these results were consistent with our results.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, D ellacà et al showed the greater potential of reactance ( X ) data compared to resistance ( R ) data to demonstrate airflow limitation: the R time course, unlike that for X , did not present clear differences between inspiration and expiration. Two articles have studied IOS in COPD [ 18 , 30 ]. Both found that reactance rather than resistance correlated most with FEV 1 , RV and TLC.…”
Section: Discussionmentioning
confidence: 99%
“…Advantages of FOT/IOS include higher sensitivity in detecting peripheral airway obstruction, short duration, and a requirement for little patient cooperation compared to spirometry, which is difficult for children, the elderly, and physically or cognitively impaired patients [94; 96]. For these reasons, FOT/IOS have proven useful in human studies for diagnosing asthma and COPD [53; 95; 98; 99; 100]. Current challenges to FOT/IOS come from its relatively recent introduction to the clinical setting, making it difficult to compare results due to the lack of standardized, healthy values.…”
Section: Methods Of Actuation For External Sourcesmentioning
confidence: 99%